2020
DOI: 10.1016/j.diabres.2020.108354
|View full text |Cite
|
Sign up to set email alerts
|

The impact of strict COVID-19 lockdown in Spain on glycemic profiles in patients with type 1 Diabetes prone to hypoglycemia using standalone continuous glucose monitoring

Abstract: Aims Spain has been one of the worst affected countries by the COVID-19 pandemic. A very strict lockdown at home was imposed with a tough restriction of mobility. We aimed to evaluate the impact of this exceptional scenario on glucose profile of patients with T1D prone to hypoglycemia using standalone continuous glucose monitoring. Methods Patients with T1D prone to hypoglycemia using multiple daily injections and either a Dexcom G5® or a Free Style Libre® CGM systems f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
70
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 13 publications
8
70
1
4
Order By: Relevance
“… 1 Earlier studies from Italy 2–5 have used CGM and flash glucose monitoring data to associate the pandemic with variable improvements in time spent in the 70–180 mg/dL target range (TIR). Similar findings have been reported for CGM users in Spain 6 and England. 7 An Israeli study noted associations between pandemic-related changes in TIR and socioeconomic status.…”
Section: Introductionsupporting
confidence: 90%
“… 1 Earlier studies from Italy 2–5 have used CGM and flash glucose monitoring data to associate the pandemic with variable improvements in time spent in the 70–180 mg/dL target range (TIR). Similar findings have been reported for CGM users in Spain 6 and England. 7 An Israeli study noted associations between pandemic-related changes in TIR and socioeconomic status.…”
Section: Introductionsupporting
confidence: 90%
“…Several groups from Italy, Spain and the UK have reported that patients with T1DM and without COVID-19 have shown no deteriorations in glycaemic control, and often even show improvements in control, during the pandemic compared with a control period before the pandemic 131 133 . During lockdown, self-reported physical activity was found to be reduced 133 , 134 and more consistent patterns of nutrient intake and sleep were found 133 ; these findings might reflect conditions under which glycaemic control is easier to achieve.…”
Section: Covid-19 and T1dmmentioning
confidence: 99%
“…Authors reported BG worsening in Brazil, India, China and African countries [16,31,33,35,36], while the opposite situation was observed in T1D groups in high income countries (HIC). With access to advanced technology, treatment, specialized services and HCPs used to digital health tools, PwD in HIC maintained or even improved their BG level during the pandemic [59,61,72,73,74]. In a study in Spain, time in range of individuals with T1D using glucose sensors increased, in comparison with the pre-pandemic period, from 57.8% to 62.5% [73], and from 55.8% to 58.2%, in Italy [61].…”
Section: Social Inequalities Hinder Effectiveness Of Measuresmentioning
confidence: 99%